The Effects of Obstetric Emergency Team Training on Patient Outcome: A Systematic Review and Meta-Analysis. Issue 4 (21st December 2022) - Brogaard, L.; Glerup Lauridsen, K.; Løfgren, B.; Krogh, K.; Paltved, C.; Boie, S.; Hvidman, L.
Abstract : ( Acta Obstet Gynecol Scand . 2022;101:25–36. doi: 10.1111/aogs.14263) Participants in simulation-based team training in obstetric emergencies often report increased confidence in their ability to manage unfolding emergencies that may present in actual practice. However, empirical data that examines the efficacy of such training on impacting clinical outcomes is incomplete. This review assesses the contribution of simulation-based training for health care providers to the outcomes of obstetric emergencies.